2010
DOI: 10.1155/2010/642412
|View full text |Cite
|
Sign up to set email alerts
|

Do Invasive Fire Ants Affect Habitat Selection within a Small Mammal Community?

Abstract: Animals must balance foraging with the need to avoid predators and risky habitats that decrease their fitness, and at the same time they must cope with competitors vying for habitat and resources. We examined how habitat selection and population density of four native small mammals were altered by the presence of red imported fire ants (Solenopsis invicta). When population size was low, hispid cotton rats (Sigmodon hispidus) and pigmy mice (Baiomys taylori) as well as white-footed mice (Peromyscus leucopus) us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…predation) and indirect effects (e.g. changes in habitat selection and avoidance behaviour) [ 7 , 8 ]. Furthermore, we observed that increased small mammal populations on S. invicta -suppressed plots were associated with an increased abundance of on-host ticks ( figure 2 ), consistent with host population regulation of tick populations [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…predation) and indirect effects (e.g. changes in habitat selection and avoidance behaviour) [ 7 , 8 ]. Furthermore, we observed that increased small mammal populations on S. invicta -suppressed plots were associated with an increased abundance of on-host ticks ( figure 2 ), consistent with host population regulation of tick populations [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ticks and small mammals transmit and maintain numerous zoonotic pathogens that are significant public health concerns. Solenopsis invicta are known to predate small mammals [ 6 ], and their presence is associated with changes in mammal foraging activity [ 7 ] and habitat selection [ 8 ] possibly mediated by changes in food resources [ 9 ]. Solenopsis invicta are also associated with reductions in tick populations [ 10 , 11 ], although effects vary between tick species [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, RIFA has been linked to decreases in native ant and invertebrate abundance and species richness in Texas and Mississippi (Epperson & Allen, 2010;Morrow et al, 2015;Porter & Savignano, 1990). Likewise, RIFA decreases songbird nest survival (Campomizzi, 2008), depredates precocial young (Haines et al, 2017) and young reptiles (Allen et al, 1994), and impacts small mammal behavior (Darracq et al, 2016;Holtcamp et al, 2010;Pedersen et al, 2003). However, other studies have shown that RIFA density neither competitively limits native ants nor changes their species richness (King & Tschinkel, 2006;Stuble et al, 2009).…”
Section: Introductionmentioning
confidence: 99%